Sosialisasi Digital Marketing Bagi Usaha Mikro Kecil dan Menengah (UMKM) di Desa Jatiluhur Purwakarta - Djatmiko, Teguh; Ahadiyat Suryana , Eka; Ubaidillah, Lutfi; Nazmah, Nazmah; Faidah, Nurul (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
MSME actors in Jatiluhur Village are currently marketing and promoting their business products still using conventional methods, namely by leaving their products in stalls, word of mouth information in this conventional way is considered not to provide satisfactory results. Changes in behavior from conventional to digital marketing have not been maximally matched by the existence of Micro, Small and Medium Enterprises, even though Micro, Small and Medium Enterprises can be trusted as one of the sectors that can encourage economic growth. The application of internet-based marketing or digital technology is one of the very positive hopes for every Micro, Small and Medium Enterprises actor so that they can compete and develop and become the center of economic power for both families, communities and countries. Micro, Small and Medium Enterprises can apply digital marketing, namely social media as a means of communicating and transacting. It is indeed very difficult at first for those who are new to the digital world, but if you are used to it, it is not too difficult, and it is also cheap and also does not need to have special skills, social media is currently considered capable of directly attracting consumer attention. The purpose of this PKM is to socialize digital marketing to Micro, Small and Medium Enterprises (MSMEs) in the Jatiluhur Purwakarta Village environment. This PKM method uses observation and socialization methods. The results of this PKM went well, this PKM program helped change marketing behavior that was still using conventional methods to change towards digitalization. This marketing digitalization socialization utilizes social media platforms that are easy to access and use so that it can increase the confidence of MSME players in promoting or marketing their selling products.